WO3−x sensitized TiO2 spheres with full-spectrum-driven photocatalytic activities from UV to near infrared. Issue 41 (6th October 2016) - Yan, Mei; Li, Guilian; Guo, Chongshen; Guo, Wei; Ding, DanDan; Zhang, Shouhao; Liu, Shaoqin
Abstract : Full-spectrum-responsive photocatalytic activities were realized by the core–shell structure of TiO2 @WO3− x . Abstract : To make full use of solar energy for photocatalytic reactions, in this work, we developed full-spectrum-responsive photocatalysts with noteworthy photocatalytic activities under either UV, visible or even near infrared irradiation for the photodegradation of methylene blue. The core–shell structure of TiO2 @WO3− x is designed from the consideration of combining the full-spectrum photo-absorption properties of WO3− x with the excellent semiconductor properties of TiO2 . As expected, the WO3− x sensitized TiO2 sphere gives rise to a prominently strong optical absorption in the whole region of 300–2500 nm and thus displays desired photocatalytic properties for the full utilization of all solar energy, especially in the unexploited NIR part, which accounts for most of the sunlight. Encouraged by the above exciting photocatalytic outcome, we then go further to propose a plausible mechanism for interpreting the NIR-driven photocatalytic properties, which is based on the hypothesis of low-valent W 5+ site induced free electrons and evidence-based ESR results.